2019
DOI: 10.3389/fbuil.2019.00086
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characterization and Vibration Analysis of a Four-Story Mass Timber Building

Abstract: Mass timber construction has been gaining momentum in multi-story residential and commercial construction sectors in North America. As taller mass timber buildings are being planned and constructed, in-situ dynamic tests of this type of construction can be performed to further validate their design and use. As part of this larger effort, an in-situ dynamic characterization testing campaign based on ambient vibration measurements was conducted on a recently constructed four-story mass timber building located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The modal properties of TTBs are difficult to predict, however it is possible to learn about the as-built modal properties of the operational TTBs. Output-only ambient vibration testing (AVT) was performed for a limited number of tall CLT buildings (see, Aloisio, Pasca, Tomasi, & Fragiacomo, 2020;Mugabo, Barbosa, & Riggio, 2019;Reynolds, Casagrande, & Tomasi, 2016;Reynolds et al, 2015), where the fundamental vibration modes were identified and compared with FE results. The AVT methods are based on measured response due to unmeasured ambient excitation, which varies with time and produces estimates that vary from one data block to another.…”
Section: Introductionmentioning
confidence: 99%
“…The modal properties of TTBs are difficult to predict, however it is possible to learn about the as-built modal properties of the operational TTBs. Output-only ambient vibration testing (AVT) was performed for a limited number of tall CLT buildings (see, Aloisio, Pasca, Tomasi, & Fragiacomo, 2020;Mugabo, Barbosa, & Riggio, 2019;Reynolds, Casagrande, & Tomasi, 2016;Reynolds et al, 2015), where the fundamental vibration modes were identified and compared with FE results. The AVT methods are based on measured response due to unmeasured ambient excitation, which varies with time and produces estimates that vary from one data block to another.…”
Section: Introductionmentioning
confidence: 99%
“…The refinement of models' calibration in the elastic range was carried out acting: on the masonry stiffness properties (more specifically on the Young Modulus E and the Shear Modulus G), for both SWs; also on the stiffness of the diaphragms, in the case of 3Muri. It should be pointed out that other sources that can contribute to the increased frequencies measured in AVT results, such as the explicit modelling of structural and non-structural elements (Soti et al 2020) or the impact of the mass distribution and of non-structural elements (Mugabo et al 2019), were neglected. Actually, the role of the non-structural elements can be relevant particularly in structures less massive and less stiff than masonry buildings.…”
Section: Refinement Of Ef Models: Calibration In the Elastic Range Through Dynamic Identificationmentioning
confidence: 99%
“…Although it has appeared on the market only recently, CLT (cross-laminated timber), also known by other trade names such as X-Lam or CrossLam, composite plywood, cross-laminated wood, BBS (Binder BrettSperrholz), or MM-BSP (Mayr-Melnhof-Brett Sperrholz Platten), has attracted considerable interest in the field of technological innovation and eco-sustainable construction materials [24,25]. CLT structures are becoming a reference model in Europe, especially in the field of multi-storey wooden constructions [26][27][28][29][30][31] and not only for residential use [32,33]. The use of the CLT is very adaptable and it allows constructing walls, floors, and roofs in various types of buildings: Multi-storey residential buildings, schools, auditoria, exhibition places, worship places, sports halls, theatres, and commercial buildings.…”
Section: Introductionmentioning
confidence: 99%